Muslim Immigrants in the Early 20th Century America: Some Have Forsaken, While Others Preserved Their Identity - Haider A Bhuiyan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This article explores the challenges that immigrant Muslims faced in pre-1965 America in their efforts to find acceptance within the American host society. To understand this phenomenon I have used the ethnographic methods of research and collecting data focusing on a Palestinian Muslim family (Abukhdeir) who came to America in 1910 and settled in Provo, Utah as Kader family and adopted Mormonism. As such, this article demonstrates that the identity crisis of early generation Muslim immigrants resulted in the following consequences: (1) Who assimilated to the prevailing American melting pot culture of mainstream society, including converting to American religions; (2) Who did not assimilate, rather escaped the pressure of assimilation by returning to their home countries and resettled there without coming back to live in America; and (3) Who both assimilated and preserved their Islamic identities, as they were the children of returnees, which coincided with the wake of multiculturalism in America in the late 1960s. These grown-up children of the returnees then shared the new process of assimilation into multicultural America, replacing melting pot culture, and affiliated with the fastest-growing Muslim communities.